"Diversity in Surgery—How Do We Change the Narrative: Pipeline to Professor?". Issue 11 (November 2021) - Johnson-Mann, Crystal N.; Butler, Paris D.; Greene, Wendy R.
The goal of our paper is to provide our perspectives on why there is a need to change the narrative in academic surgery to improve health equity by increasing the pipeline of pre-med students to professors. It is well documented that Health disparities hurt many different people, but they especially hurt Black, Indigenous, and People of color. Black men and women have a decreased life expectancy. Differences in care are associated with greater mortality among minority patients and that care provided to black patients by black physicians can lead to improved compliance with medications and care plans. The lack of black diversity in the medical profession proportional to the societal ethnic distribution is alarming. We have opportunities for improvement for recruitment, retention and promotion within the field of surgery.